Accuracy of the Radiographic Assessment of Lung Edema Score for the Diagnosis of ARDS - Zimatore, Claudio; Pisani, Luigi; Lippolis, Valeria; Warren, Melissa A.; Calfee, Carolyn S.; Ware, Lorraine B.; Algera, Anna Geke; Smit, Marry R.; Grasso, Salvatore; Schultz, Marcus J. (Frontiers in Physiology, 2021)
Background. Bilateral opacities on chest radiographs are part of the Berlin Definition for Acute Respiratory Distress Syndrome (ARDS) but have poor interobserver reliability. The ‘Radiographic Assessment of Lung Edema’ (RALE) score was recently proposed for evaluation of the extent and density of alveolar opacities on chest radiographs of ARDS patients. The current study determined the accuracy of the RALE score for the diagnosis and the prognosis of ARDS. Methods. Posthoc analysis of a cohort of invasively ventilated intensive care unit (ICU) patients expected to need invasive ventilation for > 24 hours. The Berlin Definition was used as the gold standard. The RALE score was calculated for the first available chest radiograph after start of ventilation in the ICU. The primary endpoint was the diagnostic accuracy for ARDS of the RALE score. Secondary endpoints included the prognostic value of the RALE score for ICU and hospital mortality, and the association with ARDS severity, and the PaO2/FiO2. Receiver operating characteristic (ROC) curves were constructed, and the optimal cutoff was used to determine sensitivity, specificity and the negative and positive predictive value of the RALE score for ARDS. Results. The study included 131 patients, of whom 30 had ARDS (11 mild, 15 moderate, 4 severe ARDS). The first available chest radiograph was obtained median 0 [0 to 1] days after start of invasive ventilation in ICU. Compared to patients without ARDS, a higher RALE score was found in patients with ARDS (24 [interquartile range (IQR) 16–30] vs. 6 [IQR 3–11]; P<0.001), with RALE scores of 20 [IQR 14–24], 26 [IQR 16–32] and 32 [IQR 19–36] for mild moderate and severe ARDS, respectively (P=0.166). The area under the ROC for ARDS was excellent (0.91 [0.86–0.96]). The best cutoff for ARDS diagnosis was 10 with 100% sensitivity, 71% specificity, 51% positive predictive value and 100% negative predictive value. The RALE score was not associated with ICU or hospital mortality, and weakly correlated with the PaO2/FiO2. Conclusions. In this cohort of invasively ventilated ICU patients, the RALE score had excellent diagnostic accuracy for ARDS.